The Megibung Tradition in Seraya Tengah Village, Karangasem, Bali - Pratama, I Made Marta Adi; Juniari, Ni Kadek Eni; Pranadewi, Putu Mira Astuti (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Megibung is an activity of eating by many people together in one container. Megibung is also an ancestral heritage that continues to be carried out from generation to generation, as in Seraya Tengah Village, the megibung tradition is still being carried out. Therefore, this study aims to find out how to present the megibung tradition in Seraya Tengah Village, Karangasem. The research data were obtained from interviews, observations, and documentation studies. The analysis technique of this research uses descriptive qualitative. The results of this study indicate that the presentation of megibung in Seraya Tengah Village consists of fourteen stages that must be passed in carrying out the megibung tradition and in its implementation it should not be careless because this megibung tradition has rules that should not be violated. The results of this study are expected to be used as standard rules regarding the stages of presenting megibung and can be used as a reference for the next generation.